Establishing Predictive Models for Solvatochromic Parameters of Ionic Liquids - Venkatraman, Vishwesh; Lethesh, Kallidanthiyil Chellappan (Frontiers in Chemistry, 2019)
The use of ionic liquids (ILs) in applications ranging from catalysis to reaction media in organic synthesis has been successfully demonstrated in several cases. For any given IL application, fundamental properties such as viscosity, thermal stability and toxicity have to be considered. Another property of interest is the polarity, which is a crucial indicator of solvent effects on chemical processes. Given the near-infinite combinations of cations and anions, experimental determination of solvatochromic parameters such as the hydrogen-bond acidity and basicity, and dipolarity-polarizability is prohibitive. To address this, we evaluate the utility of alternative schemes based on parameters derived from COSMO-RS (COnductor-like Screening MOdel for Real Solvents) computations. The scheme is applied to a large library of yet-to-be-synthesized ionic liquids, to identify promising candidates for applications in biomass dissolution.